Asymmetric synthesis of linezolid thiazolidine-2-thione derivatives via CS2 mediated decarboxylation cyclization. Issue 19 (7th May 2020) - Cui, De-Yun; Kong, Hong-Tao; Yang, Yi; Cai, Jianfeng; Shen, Bo-Yuan; Yan, Da-chao; Zhang, Xiu-Juan; Qu, Ying-Long; Bai, Meng-Meng; Zhang, En
Graphical abstract: Highlights: A decarboxylation cyclization method was developed. This reaction was mediated by carbon disulfide. A highly stereoselective synthesis of linezolid thiazolidine-2-thione derivatives. Selected compounds showed anticancer effects on human cancer cells. Abstract: A mild and cost-effective decarboxylation cyclization method was developed for the synthesis of chiral 5-substituted thiazolidine-2-thione derivatives from β-amino oxazolidinones. This reaction was mediated by CS2 and allowed a highly stereoselective synthesis of linezolid thiazolidine-2-thione derivatives. The chirality of the linezolid base was completely retained in the final product.